Euarchontans from Fantasia, an upland middle Eocene locality at the western margin of the Bighorn Basin. Issue 176 (March 2023) - Lundeen, Ingrid K.; Kirk, E. Christopher
Abstract: The fossil record of North American Eocene mammals is best known from relatively low-elevation 'basin center' fossil localities in intermontane depositional basins of the Western Interior. This sampling bias, largely drawn from preservational bias, has limited our understanding of fauna from higher elevation Eocene fossil localities. Here we describe new specimens of crown primates and microsyopid plesiadapiforms from a middle Eocene (Bridgerian) locality ('Fantasia') from the western margin of the Bighorn Basin in Wyoming. Fantasia has been considered a 'basin-margin' site and geological evidence suggests that it was already at a high elevation relative to the basin center at the time of deposition. New specimens were described and identified using comparisons across museum collections and published faunal descriptions. Linear measurements were used to characterize the patterns of variation in dental size. Contrary to expectations derived from other Eocene basin-margin sites in the Rocky Mountains, Fantasia has low anaptomorphine omomyid diversity and lacks evidence for the co-occurrence of ancestor-descendant pairs. Fantasia also differs from other Bridgerian sites in having low abundance of Omomys and unusual body sizes of several euarchontan taxa. Some specimens of Anaptomorphus and cf. Omomys are larger than those found in coeval sites, while specimens of Notharctus and Microsyops are intermediate in size between middle and late Bridgerian samples of these genera from basin-center sites. These findings suggest that high elevation fossil localities like Fantasia may record atypical faunal samples that should be more thoroughly explored to understand faunal dynamics during the periods of significant regional uplift like that represented by the middle Eocene record of the Rocky Mountains. Furthermore, modern faunal data indicate that species body mass may be influenced by elevation, which may further complicate the use of body mass to determine species identity in the fossil record in the regions of high topographic relief.